Methylation of PTCH1a gene in a subset of gastric cancers - Du, Peng (The WJG Press and Baishideng, 2009)
AIM: To establish if PTCH1a transcriptional regulation region (TRR) is methylated in gastric cancer and its influence in gastric tumorigenesis. METHODS: The CpG islands in PTCH1a TRR were analyzed by Methyl Primer Express v1.0 software. The region from -643 to -355 bp (the transcription initiation site of PTCH1a was designated as 0) that contained 19 CpG sites was chosen for bisulfite-sequencing PCR (BSP) and methylation-specific PCR (MSP) detection. The gastric cancer cell line AGS was treated with 5-aza-2’-deoxycytidine (5-Aza-dC; 1 μmol/L) for 3 d. Alterations in PTCH1a TRR methylation in treated AGS cells was measured through BSP clone sequences, and their PTCH1 expression was measured by quantitative RT-PCR. The cell cycle and apoptosis were observed with flow cytometry through propidium iodide (PI) staining or annexin V/PI double staining. The prevalence of PTCH1a TRR methylation was investigated in 170 gastric cancer tissue samples and the adjacent normal tissues by MSP. The correlation of PTCH1a TRR methylation with PTCH1 expression or with patients’ clinical features was analyzed. RESULTS: Methylation of PTCH1a TRR was observed in AGS cells and a subset of gastric cancer tissues (32%, 55/170), while no methylation amplification products were observed in any normal tissues by MSP. The methylation of PTCH1a TRR was correlated negatively with PTCH1 expression (Spearman’s r = -0.380, P = 0.000). However, methylation of PTCH1a TRR was not related to the gastric cancer patients’ clinical features, such as sex, age of onset, clinical stage, lymph node metastasis or histological grade. The methylation of PTCH1a TRR in AGS cells was almost converted to non-methylation after 5-Aza-dC treatment, which increased PTCH1 expression (5.3 ± 2.5 times; n = 3) and apoptosis rate (3.0 ± 0.26 times; P < 0.05; n = 3). CONCLUSION: Methylation of PTCH1a TRR is present in a subset of gastric cancers and correlated negatively with PTCH1 expression. This may be an early event in gastric tumorigenesis and a new treatment target.